PRESCRIPTION AUDIT AND EFFECTS OF COMORBIDITIES ON INDOOR COVID-19 PATIENTS OF A TERTIARY CARE TEACHING HOSPITAL - SM, MALEK; AR, KUBAVAT; A, SINGH; PR, CHABHADIYA; DD, RAJGURU; HR, PUROHIT; KN, HAJARE; TV, HADVANI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Management of COVID-19 has been a challenge to the health-care system. The COVID-19 pandemic led to prescribing a greater number of drugs for curing the disease in the initial phase of the pandemic due to a lack of understanding of the pathophysiology of COVID-19, symptomatic treatment was given as no definite treatment was available. This presented an opportunity to assess prescribing practices during the pandemic. Methods: The study presents a retrospective cohort to assess 300 random prescriptions from indoor COVID-19 patients of a tertiary care teaching hospital. The parameters analyzed in the process of the prescription audit were patients’ demographics data, prescribing standards according to the World Health Organization core indicators, clinical diagnosis with the comorbid condition, legibility of handwriting, doctor’s name and signature, and outcome of the disease. Results: Out of 300 cases analyzed, a total of 298 (99.66%) prescriptions were with antimicrobialsa total of 55 (18.3%) patients received antivirals. 167 (55.67%) admitted patients having comorbidities such as hypertension (28%) and diabetes (24.3%). Conclusion: It is observed almost every patient has received antimicrobial in the form of antibiotic or antiviral. About 18.3% of patients received antiviral drugs. The effect of co-morbidity has a significant influence on the outcome of patients having COVID-19, as in this study, mortality rate in diabetic patients is higher up to 11.48% than in non-diabetics.